Analysis of Slag Formation in Maraging Steel Weldments. (2018) - Agilan, M.; Karthikeyan, M.K.; Venkateswaran, T.; Thomas, Manu; Sivakumar, D.; Ramkumar, P.; Sankaravelayutham, P.; Venkitakrishnan, P.V.
Abstract: 18%Ni maraging steel (M250) is used in the form of welded hardware in launch vehicles. GTAW process using W2 filler wire is being followed to realise this hardware. As compared to M250, W2 filler has a lower amount of Ti and Mo. Al content is increased to 0.4 wt.% to impart high fracture toughness to the weldment. In recent past, manufacturing industries are experiencing a severe problem of slag formation in M250 weldments. Slag can be removed only by extensive inter-pass grinding. This type of slag formation in TIG welding is an unusual phenomenon and has not been reported for maraging steels. This work attempts to understand the root cause of slag formation. Extensive welding trials have been carried out on M250 steel using W2 filler wire to simulate the slag formation. The slag is hard and adherent to the weldment and it cannot be removed by simple wire brushing. Detailed analyses of slag, M250 base metal, and filler wire were carried out using SEM-EDS and XRD. Slag is found to be a variant of calcium aluminate. The main constituents are alumina (Al2O3) and calcium oxide (CaO). Based on the above observation, different contributing factors for the formation of slag and their role in the severity of slag formation are discussed. Various possible solutions to overcome this problem are also addressed.